Pediatric amyand hernia : case report in Sanjiwani Gianyar Hospital Bali-Indonesia - Luciana Luciana; Gede Eka Rusdi Antara; Made Dwi Yoga Bharatha (DiscoverSys Inc., 2019)
Introduction: Amyandâ€™s hernia (AH) is defined as protrusion of the vermiform appendix in an inguinal hernia sac, and incidence was reported only 1% of all inguinal hernias. This study aimed to share the experience of inguinal hernia repair with appendectomy for Pediatric case with non inflamed appendices.Case: A 2-year-old male came to the emergency department with a history of irreponible lump along with right scrotal tender 6 hours before admission and progressively increased. There is no specific sign of obstruction,dehydration or infection. His lump already presented since new born but with age progression the reponible complain become more frequently. Based on clinical presentation this patient did open repair of hernia as diagnostic and therapeutic, identification of appendix was non-inflamed appendix inside right scrotum, no sign of incarcerated strangulated of perforated. No Complication was reported until two-month post-operative. Surgical correction is already done with non-complication post-operative care for 2 month period.Conclusion: Pediatric Amyand Hernia is rare case (1% from all inguinal hernia) diagnostic and therapeutic could be very challenging. Open herniotomy repair and appendectomy for this case was taken with satisfying outcome.Keywords:Â pediatric, inguinal hernia, appendectomy.